Answer:
Option (c) is correct.
The solution of equation is b = 0 and b = 4.
Explanation:
The given equation,
![(5)/(3b^3-3b^2-5)=(2)/(b^3-2)](https://img.qammunity.org/2020/formulas/mathematics/college/xqwnulwkk7jvmlcqnrej5q1r0t233xums5.png)
We are required to solve the given equation for possible values of b.
Consider,
![(5)/(3b^3-3b^2-5)=(2)/(b^3-2)](https://img.qammunity.org/2020/formulas/mathematics/college/xqwnulwkk7jvmlcqnrej5q1r0t233xums5.png)
Cross multiply ,
![5(b^3-2)=2(3b^3-2b^2-5)](https://img.qammunity.org/2020/formulas/mathematics/college/xvbai178oj58s8f03y6al4v3xpsf9influ.png)
Multiply each term of LHS by 5 and RHS by 2 , we get,
![5b^3-10=6b^3-4b^2-10](https://img.qammunity.org/2020/formulas/mathematics/college/8txzxmx0s31qgtnz6i5q6wf6k2n9nme2i1.png)
Taking variable terms one sides and constant one side, we get,
![5b^3-6b^3+4b^2=10-10](https://img.qammunity.org/2020/formulas/mathematics/college/si2ydmymf3lwg4xm2uljeb86u78ddru4to.png)
Solving , we get,
![-b^3+4b^2=0](https://img.qammunity.org/2020/formulas/mathematics/college/cxdmymyosy4fh7gq6gmq3ixu4kafwf1ic0.png)
Taking
common from both terms, we get,
![b^2(4-b)=0](https://img.qammunity.org/2020/formulas/mathematics/college/joi39fq6o6yw37dckxtjefxj2ix6lk9zg2.png)
and
![\Rightarrow 4-b=0](https://img.qammunity.org/2020/formulas/mathematics/college/gfk5hc7qldhuct40bou5rgnqijueni5nun.png)
and
![\Rightarrow b=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wdvxnj067wwlzt9kahn6epj9xoa2lbz2oz.png)
Thus, Option (c) is correct.
The solution of equation is b = 0 and b = 4.